(3GdeSJbUi aj CeKGd GdYQHs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3GHh eMeO Ydi Hf CSYO TaQhg s)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CKdL Hg UOhQfG ef HQO Gdjbjf GdJUfja eVGQ JfUH Edjg Njd GdSHGb aUGOaJ GdTYHI GdJi gi CeKGd GdYQH s
(3BNQgG (B:s
(3jVQH def jaSO hdG jUdM ebGd GdeUfa bO GfJgi Hi JCjjO Gddg hMSf JSOjOg Edi GdZGjI GdJi CLQjJ fMhgG hGdMeO ddg s
(3HgG fXGe JYbjHIs
(3aQZ GdeDda ef JCdjag SfI (B499s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
Keywords: (3GdCOHs